Study the effect of Heavy Oil Fuel Ash on the geotechnical properties of clay soil - Ousta, Rami; Tawalo, Ali (Acta Technica Jaurinensis, 2021)
Power stations are widely spread in Arabic Syrian Republic, unlike most of power stations in the world that work by using coal as the operating fuel, most of Syrian power stations depend on the heavy fuel oil to generate electricity. Although there are a lot of studies about use of the fly ash produced from burning coal, the fly ash resulted by using heavy fuel oil as an operating material for the power stations had less attention. This paper aims to study the effect of this type of fly ash on the geotechnical properties of the clay soil and comparison it with the effect of fly ash resulted by power stations that use the coal. Two percentages of heavy oil fuel ash were mixed with the soil 5% and 10% of the dry soil weight with two curing periods 7 and 28 days. The results indicated that adding heavy oil fuel ash to the soil will decrease the cohesion in addition to increase the internal friction angle. There is not clear effect of the curing periods and the increase in the percentage of fly ash on the Atterberg limits.